2020
DOI: 10.1177/0731684420916534
|View full text |Cite
|
Sign up to set email alerts
|

Development of beneficial residual stresses in glass fiber epoxy composites through fiber prestressing

Abstract: The undesired residual stresses in fiber reinforced polymer composites are developed during their manufacturing processes due to the thermal and chemical shrinkage of the polymer matrix, which negatively affect the performance of the composites. Applying tensile stress to the reinforcement fibers during the curing of the matrix can reduce or eliminate the undesired residual stresses. Furthermore, the undesired tensile residual stress within the matrix can be replaced with beneficial compressive residual stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…16,20,21 Similar to the prestressed concrete, the initial applied prestress in the fiber undergoes two types of losses: (1) instantaneous losses or short-term losses and timedependent losses or long-term losses. In a previous study, Mohamed et al 14 reported two sources of the instantaneous prestress losses. The curing-induced residual stresses that develop during the cooling of composite from the high curing temperature to room temperature is the first source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,20,21 Similar to the prestressed concrete, the initial applied prestress in the fiber undergoes two types of losses: (1) instantaneous losses or short-term losses and timedependent losses or long-term losses. In a previous study, Mohamed et al 14 reported two sources of the instantaneous prestress losses. The curing-induced residual stresses that develop during the cooling of composite from the high curing temperature to room temperature is the first source.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the bond between the fiber and matrix, the tensile residual stress within the fiber is balanced by producing compressive residual stress into the surrounding matrix. 8,10,13,14 The elastic method was the only known method of producing prestressed FRP composites until the late 1990s when Fancey invented a new prestressing method relies on using fibers with a viscoelastic behavior such as nylon. 15 The difference in this method is that the tension force is applied to the fiber for a particular time and released before molding the pre-tensioned fiber into the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Glass fibers have better thermal stability and dimensional stability that initiates their usage in various technological applications [5,6]. In the last few years, material researchers focus on developing advanced materials to decrease fuel [7][8][9][10] consumption in transport industries [11][12][13]. Hence, incorporation of these fibers in polymer material will confidently improvise the stiffness, flexibility, and strength.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] For this reason, recent studies have investigated the incorporation of glass fibers in petrochemical-based thermoset matrices to overcome these disadvantages and improve their overall mechanical properties. [12][13][14] Today, polyester, [15][16][17] epoxy, [18,19] and phenolic [20,21] resins are the most widely used thermoset matrices for natural fiberreinforced polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%